Populations of Nepenthes natural hybrids might overcome secondary forest in Ban Thung Tuek, Ko Kho Khao, Phangnga Province, Thailand - Jantaraprasit, Napat; Ngernsaengsaruay, Chatchai; Thunthawanich, Raweewan (Agriculture and Natural Resources, 2024)
Importance of the work: Niche-specific adaptations were highlighted through addressing the ecological dynamics and adaptive strategies of Nepenthes in Melaleuca cajuputi-dominated secondary forests. Objectives: To assess the community structure and distribution of Nepenthes across environmental gradients. Materials & Methods: Three 20 m × 50 m plots were established across a gradient from peat swamp forest to dry land, subdivided for detailed analysis of the tree, sapling and Nepenthes populations, including the Importance Value Index for plant community analysis. Results: Two species, one variety and two natural hybrids were identified: Nepenthes andamana and N. mirabilis var. globosa and two Nepenthes natural hybrids: N. mirabilis × N. andamana and N. mirabilis var. globosa × N. mirabilis var. mirabilis. Distinct habitats were identified fostering diverse plant communities, with Melaleuca cajuputi as the dominant tree species. All Nepenthes species and natural hybrids exhibited varied distribution and abundance, influenced by habitat conditions. The highest abundance was for N. mirabilis var. globosa × N. mirabilis var. mirabilis, mainly in intermediate and dry zones, with major implications for species survival and distribution under varying environmental conditions and anthropogenic pressures. Main finding: Habitat-driven diversity in Nepenthes was uncovered, emphasizing the importance of ecological tolerance. The prevalence of N. mirabilis hybrids indicated genetic introgression risks, urging the need for focused conservation efforts to preserve species.